Evaluation of stocking density for pond aquaculture with special reference to survival and production in Tiruchirapalli, Tamil Nadu - SHARMA, PAWAN KUMAR; KUMAR, J STEPHEN SAMPATH; MANIKANDAVELU, D (The Indian Journal of Animal Sciences, 2021)
The present study was conducted to optimize the stocking density for pond fish culture. For this purpose, two different stoking densities, i.e. 18000 (T1) and 7600 per hectare (T2) were tested using earthen ponds of 0.25 ha size. Both ponds were stocked uniformly with 4 carp species, viz. Catla catla, Labeo rohita, Cirrhinus mrigala, and Cyprinus carpio in equal proportions and fed on commercial pellet feed (20% crude protein). The estimated gross production was found higher in pond T2 (4166 kg/ha) than that of T1 (4000 kg/ha). The T2 pond showed a net estimated additional yield of 187.76 kg/ha, which was 4.74% higher than that of T1 pond. A higher survival rate was observed in T2 (59.17%) than that of T1 (27.68%), which was statically significant. Further, the ADG (average daily growth) rate of fishes in T2 was 0.70 kg/ha/day higher than that of T1. The study revealed that there is an inverse relation between the stocking density of fishes and production rate. Considering the growth/production rate and survival in present study, a seed stocking density of 7600 per ha is recommended for farm pond aquaculture.